2001
DOI: 10.1093/rheumatology/40.8.876
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin‐15 is elevated in systemic lupus erythematosus

Abstract: Serum IL-15 may in part be responsible for the immunological abnormalities seen in active SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 41 publications
5
68
0
3
Order By: Relevance
“…In autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis, both levels of IL-15 and IL-21 were concomitantly elevated, and were associated with disease activity [46][47][48][49]. Our data suggest that elevated IL-15 and IL-21 in autoimmune patients could lead to hyperactivation of B cells facilitating PC differentiation that may harbor autoreactive PCs.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis, both levels of IL-15 and IL-21 were concomitantly elevated, and were associated with disease activity [46][47][48][49]. Our data suggest that elevated IL-15 and IL-21 in autoimmune patients could lead to hyperactivation of B cells facilitating PC differentiation that may harbor autoreactive PCs.…”
Section: Discussionmentioning
confidence: 85%
“…Both IL-15 and IL-21 are abundant in human tonsils, and sources for these cytokines could be macrophages and Tfh cells, respectively. Several studies including ours have shown the importance of macrophages in driving PC development in vitro and in vivo [7][8][9][10] In autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis, both levels of IL-15 and IL-21 were concomitantly elevated, and were associated with disease activity [46][47][48][49]. Our data suggest that elevated IL-15 and IL-21 in autoimmune patients could lead to hyperactivation of B cells facilitating PC differentiation that may harbor autoreactive PCs.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum IL-15 levels have been described in patients with chronic progressive multiple sclerosis, 52 type I diabetes, 53 and systemic lupus erythematosus. 54 Elevated local amounts of IL-15 have also been observed at sites of inflammation, 55,56 including the synovium in rheumatoid arthritis, 57,58 and anti-IL-15 therapy is effective in rheumatoid arthritis patients. 59 Consistent with this, rheumatoid arthritis is also associated with elevated serum and synovial fluid NO.…”
Section: Discussionmentioning
confidence: 99%
“…Tokano, et al 3 reported that the levels of IL-12 in SLE patients were significantly higher than those in normal subjects; Aringer, et al 4 showed that IL-15 was elevated in SLE sera and was correlated significantly with Bcl-2 expression. Segal, et al 5 reported that administration of IL-12 to aging mice reversed their Th1/Th2 cytokine profile and thus rendered them vulnerable to induction of experimental SLE; and Bo, et al 6 demonstrated that elevated expression of transmembrane IL-15 in immune cells correlated with the development of murine lupus, suggesting that Th1-associated cytokines might play a crucial role in the pathogenesis and development of SLE.…”
Section: To the Editormentioning
confidence: 99%